2015
DOI: 10.1080/00918369.2015.1078651
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction, Self-Esteem, and Loneliness Among LGB Adults and Heterosexual Adults in China

Abstract: Low levels of life satisfaction have been linked to low self-esteem and loneliness, but this association has never been tested directly in LGB (lesbian/gay/bisexual) populations. We compared 275 Chinese LGB adults to 275 demographic-matched Chinese heterosexual controls on life satisfaction, self-esteem, and loneliness. LGB adults reported lower levels of self-esteem and higher levels of loneliness than heterosexuals, but similar levels of overall life satisfaction. Self-esteem partially mediated (but did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
3
22
0
1
Order By: Relevance
“…A bifobia pode impactar as crenças a respeito da bissexualidade (como "bissexualidade é uma fase" e "pessoas bissexuais são promíscuas", por exemplo (Diener, Emmons, Larsen, & Griffin, 1985). Em pessoas LGB, a autoestima e a solidão estão, respectivamente, positiva e negativamente associadas à satisfação com a vida (Hu, Hu, Huang, & Zheng, 2016 baixas diferenças entre os grupos se justificam: sendo a orientação sexual apenas uma característica dentre muitas que são parte da realidade humana, e a única (dentre as variáveis analisadas) que dá às respondentes experiências de vida diferentes, devido ao estigma associado às orientações não heterossexuais.…”
Section: /13unclassified
“…A bifobia pode impactar as crenças a respeito da bissexualidade (como "bissexualidade é uma fase" e "pessoas bissexuais são promíscuas", por exemplo (Diener, Emmons, Larsen, & Griffin, 1985). Em pessoas LGB, a autoestima e a solidão estão, respectivamente, positiva e negativamente associadas à satisfação com a vida (Hu, Hu, Huang, & Zheng, 2016 baixas diferenças entre os grupos se justificam: sendo a orientação sexual apenas uma característica dentre muitas que são parte da realidade humana, e a única (dentre as variáveis analisadas) que dá às respondentes experiências de vida diferentes, devido ao estigma associado às orientações não heterossexuais.…”
Section: /13unclassified
“…LGB Chinese consistently report family pressure as the greatest challenge they face in their daily lives. (Hu et al, 2016;UNDP, 2016;Liu, 2013;Chow and Cheng, 2010;Engebretsen, 2009). Family pressure can include (but is not limited to) the explicit or implicit expectation to conform to traditional norms, notably opposite-sex marriage The one-child policy, eldercare, and LGB Chinese 5 and procreation.…”
Section: Family Pressure On Lgb People In China and Beyondmentioning
confidence: 99%
“…There has been limited survey research into family pressure amongst LGB Chinese, but some recent work build upon this author's findings. Two recent 2016 surveys of lesbian, gay and bisexual Chinese found that discrimination was most frequently experienced at home from their families (Hu et al, 2016;UNDP, 2016).…”
Section: Family Pressure On Lgb People In China and Beyondmentioning
confidence: 99%
See 2 more Smart Citations